2015
DOI: 10.1186/s13071-015-1031-y
|View full text |Cite
|
Sign up to set email alerts
|

First report outside Eastern Europe of West Nile virus lineage 2 related to the Volgograd 2007 strain, northeastern Italy, 2014

Abstract: BackgroundWest Nile virus (WNV) is a Flavivirus transmitted to vertebrate hosts by mosquitoes, maintained in nature through an enzootic bird-mosquito cycle. In Europe the virus became of major public health and veterinary concern in the 1990s. In Italy, WNV re-emerged in 2008, ten years after the previous outbreak and is currently endemic in many areas of the country. In particular, the northeastern part of Italy experience continuous viral circulation, with human outbreaks caused by different genovariants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 20 publications
(19 reference statements)
2
38
0
Order By: Relevance
“…() after WNV isolation in Vero cells. Comparisons with published sequences were performed by searches in the NCBI BLAST database, and sequences were aligned by Clustal W. Phylogenetic analyses showed that the WNV lineage 2 isolated in Spain belonged to the Central/Southern European WNV lineage 2 cluster (Ravagnan et al., ), where WNV strains detected in the last years in other northern goshawks, humans, and mosquitoes are included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…() after WNV isolation in Vero cells. Comparisons with published sequences were performed by searches in the NCBI BLAST database, and sequences were aligned by Clustal W. Phylogenetic analyses showed that the WNV lineage 2 isolated in Spain belonged to the Central/Southern European WNV lineage 2 cluster (Ravagnan et al., ), where WNV strains detected in the last years in other northern goshawks, humans, and mosquitoes are included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The animal tested positive by cELISA and negative by SNT, but 1-month later antibodies against WNV were detected by SNT, evidencing seroconversion, and WNV transmission within Vallcalent-WRC. Serum samples from other 13 bearded vultures were positive by cELISA, and two were confirmed by SNT at the CVL (titers between 1/20 and 1/40).A fragment of 930 nt of the NS5 gene from the first northern goshawk was sequenced by Sanger's method using the primers described byVázquez et al (2012) after WNV isolation in Vero cells.Comparisons with published sequences were performed by searches in the NCBI BLAST database, and sequences were aligned by Clustal W. Phylogenetic analyses showed that the WNV lineage 2 isolated in Spain belonged to the Central/Southern European WNV lineage 2 cluster(Ravagnan et al, 2015), where WNV strains detected in the last years in other northern goshawks, humans, and mosquitoes are included (Figure 1).The detection in the northern goshawk was the first WNV outbreak reported in the North of the Iberian Peninsula. Furthermore, until now, all WNV cases reported there had been caused by WNV lineage 1.…”
mentioning
confidence: 99%
“…The spatiotemporal pattern of these sequential events suggests that migratory bird species play a role in the dispersal of WNV from endemically infected areas. The exceptional potential for geographic spread of WNV by migratory birds is demonstrated by the North Italian emergence of the lineage 2 Volgograd strain previously found only in the Black Sea region (Ravagnan et al 2015).…”
Section: West Nile Virus Infections By Karoly Erdelyimentioning
confidence: 99%
“…The Russian strain, which has been responsible for human outbreaks in the Volgograd and Astrakhan regions since 2007, has also spread to Europe; it has been involved in human infections in Romania since 2010 [14] and, in 2014, it was detected in mosquito pools collected in north-eastern Italy but was not associated with human infections [15]. WNV lineage 2 is currently responsible for the vast majority of human WNV infections reported in Europe.…”
Section: Introductionmentioning
confidence: 99%